THE CONTRIBUTIONS OF DANCE IN THE DEVELOPMENT OF SOCIO-EMOTIONAL SKILLS OF STUDENTS WITH AUTISTIC SPECTRUM DISORDER (ASD): The contributions of dance in the development of socio-emotional skills of students with autistic spectrum disorder (ASD) - Pereira, Renata Alves Maciel (2024)
Adapted to the needs of students with autism spectrum disorder (ASD), dance offers significant benefits for this target audience. To this end, this article aimed to investigate the contributions of dance in the process of developing the socio-emotional skills of students with ASD, enrolled in elementary school I in the public network. The guiding problem question of this study is: how can dance contribute to the process of developing the socio-emotional skills of students with Autism Spectrum Disorder? It was considered that dance has the potential to contribute to the socialization process of students with Autism Spectrum Disorder. It is an applied, descriptive and qualitative-quantitative methodology initiated by a bibliographical study to approach the topic, followed by a field study at the Luz do Amanhecer Special Education Center, with the elaboration of a Technical-Technological product based on the research. The results show that dance offers multiple benefits for the development of socio-emotional skills in students with ASD. Emotional regulation, self-confidence, self-esteem and motor coordination, dance can be a powerful and effective tool in supporting the integral development of these students with ASD.